PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN PUZZLE TERHADAP KEMAMPUAN SISWA MEMAHAMI BENTUK BANGUN DATAR DI KELAS 2 SD KEPONG MALAYSIA - Arisanti, Fitri; Nasution , Dewi Kesuma (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study is based on the low interest in learning students, especially in mathematics, and the limited ability of students to understand flat shapes. The purpose of this study was to evaluate students' abilities before and after the implementation of puzzle learning media, and to identify the impact of using the media on students' understanding in grade 2 of Kepong Elementary School, Malaysia. The population and sample of the study consisted of 20 grade 2 students of Kepong Elementary School, Malaysia. Data collection was carried out through a test that included 10 questions. Data analysis included Validity Test, Reliability Test, and Hypothesis Test. The results of the Validity Test showed that 9 questions were valid, while 1 question did not meet the validity criteria with a coefficient value of 0.299. Meanwhile, the results of the Reliability Test showed that 9 valid questions had a Cronbach's Alpha value of 0.798, which indicated a good level of reliability. Hypothesis Testing through paired sample tests produced a p value of 0.000, which was smaller than 0.05, so H1 was accepted. This shows that there is a significant influence from the use of puzzle-based learning media on increasing students' understanding of data shapes in class 2 of Kepong Elementary School, MalaysiaKeywords: Puzzle Media, Understanding, Flat Building